Plant conservation biotechnology - Benson, Erica E; Ed (Taylor & Francis, 1989)
Introduces biotechnological techniques which are currently used to conserve horticultural and crop plant germplasm, forest tree genetic resources, endangered plant species, and plant cell culture collections. Covers techniques and applications.